Upaya Non Litigasi Dalam Penyelesaian Sengketa Penyerobotan Tanah - Mohamad Jusuf Husain Isa; Nur Zakiah; Fitri Fuji Astuti Ruslan (PT FORMOSA CENDEKIA GLOBAL, 2022)
Non litigation efforts in dispute revolution of land invasions (study implementation of article 1 paragraph (10) law no. 30 in 1999 in the manuba village, malusetasi district, district of barru). In this paper, the authors raised the issue of Non-Litigation Efforts In Dispute Resolution of land invasions. The choice of the theme motivated by resolving disputes in court that takes a long time and certainly need much money, as well as the final result determine the losing and the winning side, because the principle of Indonesian society are conference and kinship. According to Article 1, paragraph (10) of Law no. 30 of 1999 on arbitration and alternative dispute resolution, then the public can choose dispute revolution through non-litigation dispute, namely mediation, negotiation, conciliation, consultation, and expert assessment. This thesis uses sociological and juridical approach this type of research is empirical legal research. The primary and secondary law materials that authors obtained will be analyzed using qualitative descriptive analysis techniques. As a population are people who have experienced got a case of land invasions, the head of village, and advocate. Primary data collection technique is interview, while secondary data use library research. From the results of research by the method above, the authors obtained answers to existing problems that non-litigation efforts in the resolution of disputes in the village Manuba of land invasions in accordance with the wishes of the parties and ended in peace. Mediation in the dispute resolution process of annexation of land succeed in accordance with the wishes of the parties.